105 Patient Satisfaction Reviews for 967 Spine Neurosurgeons. (1st April 2022) - Agarwal, Nitin; Gupta, Arjun; Gupta, Radhika; White, Michael D.; Reddy, Vamsi; Chang, Yue-Fang; Agarwal, Prateek; Alan, Nima
Abstract : INTRODUCTION: Patients are increasingly relying on independent physician-rating websites (PRWs) to obtain information about healthcare providers. Healthgrades.com is a widely used PRW which allows patients to rate physicians on various metrics of performance and quality-of-care. METHODS: This study categorically investigated the correlations between demographics of spine neurosurgeons and online ratings on Healthgrades to better understand the factors driving patient satisfaction in spine surgery in the United States. RESULTS: A total of 967 spine neurosurgeons were included in the study cohort. Patient satisfaction did not correlate with gender, Ph.D. acquisition, academic status, or academic rank. Among those who were academic surgeons, completion of fellowship training was associated with higher ratings. Geographical location of practice did not influence patient satisfaction. Prolonged wait time was an independent predictor of decreased patient satisfaction and was a key confounding variable underlying trends seen with advanced career duration and age. CONCLUSION: Overall, patients rated spine neurosurgeons highly favorably on Healthgrades.com . Due to the emerging role of PRWs in locating and assessing providers, it is important for both patients and clinicians to understand the factors that impact patient experience.